Recovery from severe persistent COVID-19 without evidence of an anti-SARS-CoV-2 antibody response in a man with mantle cell lymphoma treated with rituximab - Horiuchi, Hiroshi; Sasaki, Hiroaki; Miyazaki, Kazuhito; Miyata, Nobuyuki; Yoshimura, Yukihiro; Tachikawa, Natsuo (Journal of infection and chemotherapy : official journal of the Japan Society of Chemotherapy, 2022)
Lymphoma has been reported to worsen the prognosis of COVID-19 partly because it disturbs the normal production of antibodies. We treated a man with mantle cell lymphoma treated with rituximab, who developed severe COVID-19 with viral shedding that lasted for 78 days. He stayed in the intensive care unit for 28 days and did not respond to any treatment against COVID-19. His increased oxygen demand at rest eventually resolved despite the absence of anti-SARS-CoV-2-IgG. This case illustrates that recovery from COVID-19 can occur without antibody production, and that even patients with an inability to produce antibodies can recover from severe COVID-19. It also illustrates that lymphoma patients who develop severe COVID-19 while on rituximab therapy can recover from a prolonged viral shedding state if the acute lung injury can be overcome.